SYMPOSION - - Silvio Menghini (Firenze University Press, 2012)
The "Symposion" project was launched in 2008 through collaboration between the Centre for the Strategic Development of the Italian Wine Sector (U niCeSV) of the University of Florence, within the framework of the activities of the Culture and Territory Observatory, and the Tuscan Archaeological Commission (National Archaeological Museum of Florence). The project involves the promotion of seminars and conferences, both in Italy and abroad, accompanied by exhibitions and speci c publications offering insight into issues related to the presence of the vine and wine among the peoples of the Mediterranean area, from prehistoric times up to the present, and analysis of the signi cance of the close relationship between product, land and culture.